Nurse's Foci of Commitment Model to Decrease Turnover Intention - Nursalam Nursalam; Nurul Hikmatul Qowi; Tri Johan Agus Yuswanto; Ferry Efendi (International Journal of Public Health Science (IJPHS), 2022)
The hospital is an organization in the service sector with nurses as the main hospital resource. Increasing the commitment of the nurses was one of the ways used to retain nurses. This study explained nurse’s foci of commitment model to decrease turnover intention.This study used a cross-sectional approach. Variables in this study included nurse characteristics, job characteristics, work experience, organizational factors, nurse commitment, and turnover intention. The population was nurses who have worked in Islamic hospital in Surabaya, Indonesia. The 119 nurses taken as sample based on simple random sampling. Data collected using questionnaires and analyzed using partial least squares (PLS). Nurse characteristics influenced nurse commitments (path coefficient=0.252; t=2.953) and turnover intention (path coefficient= -0.239; t=2.458). Job characteristics influenced nurse commitments (path coefficient=0.190; t=2.409) and turnover intention  (path coefficient= -0.183; t=2.107). Work experience influenced nurse commitments (path coefficient=0.208; t=2.231) and turnover intention (path coefficient= -0.153; t=1.964). organizational factors influenced nurse commitments (path coefficient=0.218; t=2.170) and turnover intention  (path coefficient= -0.174; t=2.330). Nurse commitment influenced turnover intention (path coefficient= -0.226; t=2.084). The nurse's commitment as moderate these factors in reducing turnover intention. The influence of job satisfaction, nurse commitment, and perceived  organizational support to turnover intention needs further research